2009
DOI: 10.1097/mph.0b013e3181979c70
|View full text |Cite
|
Sign up to set email alerts
|

13-cis Retinoic Acid Treatment of a Patient With Chemotherapy Refractory Nephroblastomatosis

Abstract: A 9-month-old girl presented with massive bilateral diffuse nephroblastomatosis. After response to actinomycin D and vincristine over a period of 1 year, the nephroblastomatosis continuously progressed under this treatment. As retinoic acid signaling is critical for normal renal development and nephroblastomatosis seems histologically as undifferentiated embryonal tissue, we added 13-cis retinoic acid to the chemotherapy regimen. Three months thereafter, kidney volumes declined significantly over a period of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…Together with the strong growth suppression observed in vitro for all retinoids tested this clearly hints at a possible therapeutic utility of such a treatment. This is supported by the impressive clinical success of retinoid treatment in one case report of nephroblastomatosis, a WT precursor lesion, where a significant decline of kidney volumes was observed over a period of 1 year [11]. The comparatively poor response seen for ws592, a culture derived from mesoblastic nephroma, an early childhood tumor separate from WT, suggests that the effects observed with our cultures of classical WT may be rather specific and not due to general or unspecific effects of retinoids on cultured human cells and it may further set this tumor apart from classical WT.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Together with the strong growth suppression observed in vitro for all retinoids tested this clearly hints at a possible therapeutic utility of such a treatment. This is supported by the impressive clinical success of retinoid treatment in one case report of nephroblastomatosis, a WT precursor lesion, where a significant decline of kidney volumes was observed over a period of 1 year [11]. The comparatively poor response seen for ws592, a culture derived from mesoblastic nephroma, an early childhood tumor separate from WT, suggests that the effects observed with our cultures of classical WT may be rather specific and not due to general or unspecific effects of retinoids on cultured human cells and it may further set this tumor apart from classical WT.…”
Section: Discussionmentioning
confidence: 88%
“…in childhood neuroblastoma [9,10]. Until today next to nothing is known about retinoids as therapeutic agents in WT, since only one case of 13 cis -RA treatment of nephroblastomatosis, a WT precursor lesion, [11] and administration of fenretinide in one patient with WT [12] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…treated cultured Wilms tumor cells with ATRA and observed the reversion of gene expression patterns that are associated with high risk and relapse. There is in addition a case report of a child being successfully treated with 13‐cis retinoid after a relapse of a bilateral nephroblastomatosis . Especially in tumors that are resistant to conventional therapy, ATRA‐induced growth inhibition might hence be used as alternative or additional therapeutic intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Interstitial fibrosis is the main cause of end stage renal failure. Retinoids are believed to inhibit inflammatory and proliferative pathways (24)(25)(26)(27)(28). Lehrke et al (25) suggested that the natural retinoic acid and 13cis retinoic acid conserve renal formation and function in rat mesangioproliferative glomerulonephritis and that all retinoid agonists with different subtypes are profoundly efficient in reducing renal damage and proliferation of mesangial cells.…”
Section: Discussionmentioning
confidence: 99%